Cerimetric determination of simvastatin in pharmaceuticals based on redox and complex formation reactions - Basavaiah, Kanakapura; Devi, Okram Zenita (Eclética Química, 2008)
Two sensitive spectrophotometric methods are described for the determination of simvastatin (SMT) in bulk drug and in tablets. The methods are based on the oxidation of SMT by a measured excess of cerium (IV) in acid medium followed by determination of unreacted oxidant by two different reaction schemes. In one procedure (method A), the residual cerium (IV) is reacted with a fixed concentration of ferroin and the increase in absorbance is measured at 510 nm. The second approach (method B) involves the reduction of the unreacted cerium (IV) with a fixed quantity of iron (II), and the resulting iron (III) is complexed with thiocyanate and the absorbance measured at 470 nm. In both methods, the amount of cerium (IV) reacted corresponds to SMT concentration. The experimental conditions for both methods were optimized. In method A, the absorbance is found to increase linearly with SMT concentration (r = 0.9995) whereas in method B, the same decreased (r = -0.9943). The systems obey Beer’s law for 0.6-7.5 and 0.5-5.0 μg mL-1 for method A and method B, respectively.